Recent advances in transition-metal-free carbon-carbon and carbon-heteroatom bond-forming reactions using arynes - Bhunia, Anup; Yetra, Santhivardhana Reddy; Biju, Akkattu T. (Chemical Society Reviews, 2012)
This tutorial review is aimed at highlighting recent developments in transition-metal-free carbon-carbon and carbon-heteroatom bond-forming reactions utilizing a versatile class of reactive intermediates, viz., arynes, which hold the potential for numerous applications in organic synthesis. Key to the success of the resurgence of interest in the rich chemistry of arynes is primarily the mild condition for their generation by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates. Consequently, arynes have been employed for the construction of multisubstituted arenes with structural diversity and complexity. The versatile transition-metal-free applications of arynes include cycloaddition reactions, insertion reactions and multicomponent reactions. In addition, arynes have found applications in natural product synthesis. Herein, we present a concise account of the major developments that occurred in this field during the past eight years.

Recent advances in the N-heterocyclic carbene (NHC)-organocatalyzed stetter reaction and related chemistry - Yetra, Santhivardhana Reddy; Patra, Atanu; Biju, Akkattu T. (Synthesis‐Stuttgart, 2015)
Recent developments in the N-heterocyclic carbene (NHC)-catalyzed umpolung of aldehydes followed by their interception with activated carbon–carbon double bonds, namely the Stetter reaction, are presented. Advances in the inter- and intramolecular versions of this reaction, enantioselective transformations as well as the use of unactivated olefins in this type of reaction are discussed.